The Use of Technology in Capturing Various Traditional Motifs and Ornaments: A Case Study of Batik Fractal, Indonesia and TUDITA-Turkish Digital Textile Archive - Gondoputranto, Olivia; Dibia , I Wayan (Humaniora: Journal of Indonesia Culture and Society, 2022)
Technological development and digitalization were often identified as the cause of traditional culture elimination. There was an antithesis when it came to technology and digitalization. Therefore, with these two representative cases, the research aimed to show that these developments did not eliminate existing traditions but could instead preserve the almost gone cultures. The material objects were traditional textile motifs, namely Indonesian batik and Turkish Sumerbank, while a descriptive qualitative method was applied via a collective case study. First, it involved batik fractal by Piksel Indonesia, where the community used an algorithm, and the Turkish Digital Textile Archive (TUDITA) by Izmir Economic University. These two case studies were selected based on the same material object and traditional motifs but using different technological application processes. The data sources were observation and reviews of literature and audiovisuals. At the same time, the analysis of the two cases was described, analyzed, and performed via Contemporary Cultural theory in the digital age perspective, explicitly using the three indicators for viewing cultural perspectives in the digital era by Piliang. Each indicator was applied to analyze the technology implementation for each case and afterward showed the impact of technology implementation for each indicator. Subsequently, the results show that the traditional Indonesian batik and Turkish Sumerbank motifs are successfully preserved by technology. Batik fractal shows that it has been a great help for the batik artisans to recreate the traditional motifs by using Jbatik software. The traditional batik motifs can be preserved and reproduced into other implementations. While TUDITA also shows how the process of digitalization can restore the lost traditional motifs to build a digital archive of traditional motifs and results in more explorative implementation. Furthermore, although both cases use different technological methods, their implementation produces a new form of traditional textile synthesis without eliminating the essence of the local values contained.